Assessing the Influence of Language Anxiety on English Oral Performance Among Mainland Chinese Postgraduates in a Malaysian Public University. - May , Lai See; Mohd Firdaus Kozako, Intan Nurul’Ain; Rosly, Rohazlyn; Abdul Malek, Nur Ain; Wan Azib, Wan Nor Hazimah (Journal of Islamic, Social, Economics and Development, 2024)
As international student mobility continues to rise, language challenges have become a significant concern, especially for Mainland Chinese postgraduates studying in non-native English-speaking countries like Malaysia. This study investigates the impact of language anxiety on English oral performance among these students at Universiti Teknologi MARA Cawangan Kelantan (UiTMCK). Using semi-structured focus group interviews, the research identifies key factors contributing to language anxiety, including cultural adaptation difficulties, fear of negative evaluation, and limited opportunities for English-speaking practice. The findings reveal that language anxiety significantly hinders oral performance, leading to speech hesitations, avoidance behaviors, and communication errors. The study's significant contribution lies in addressing a gap in the literature by focusing on Mainland Chinese students in Southeast Asia, offering insights that could inform targeted language support programs to enhance oral communication skills and reduce anxiety. Additionally, the study provides recommendations for future research to further explore these issues among other international student populations.